Development of antibacterial magnetic clay-based nanocomposites for water treatment - Horue, Manuel; Barraqué, Facundo; Montes, María Luciana; Zelaya-Soulé, María Emilia; Morantes, César Fernández; Urruchua, Florencia Camila; Correa, Hilda Edith; Castro, Guillermo Raul; Fernandez, Mariela Alejandra (Comptes Rendus. Chimie)
Organoclays were prepared using Argentinean montmorillonite (Mt), hexadecyltrimethylammonium, or benzalkonium chloride at different concentrations. Surfactant incorporation, a key factor in biocide capacity, was estimated using interlayer space and thermogravimetric analysis (TGA). Subsequently, Fe oxides were grown on the organoclays. Saturation magnetization indicated that all magnetic composites could respond to an external magnetic field. Inhibition experiments showed high antibacterial activity against Enterococcus faecium, Escherichia coli, and Salmonella typhimurium. The synthesized nanocomposites loaded with 150% CEC (cation exchange capacity) of hexadecyltrimethylammonium were the most effective. Those results were more precisely investigated using the viable plate count method. The magnetic materials had a similar antimicrobial effect to those without magnetic properties, indicating that Fe oxides can be nucleated to impart a magnetic response without affecting the biocide properties. The organoclays showed higher antibacterial activity against E. coli than against the other bacteria assayed. In addition, the agar disk-diffusion method revealed that antimicrobial agents were not released from clays, which is a relevant fact in the water treatment process.